2020
DOI: 10.1038/s41598-020-65876-3
|View full text |Cite
|
Sign up to set email alerts
|

Ensilicated tetanus antigen retains immunogenicity: in vivo study and time-resolved SAXS characterization

Abstract: our recently developed ensilication approach can physically stabilize proteins in silica without use of a pre-formed particle matrix. Stabilisation is done by tailor fitting individual proteins with a silica coat using a modified sol-gel process. Biopharmaceuticals, e.g. liquid-formulated vaccines with adjuvants, frequently have poor thermal stability; heating and/or freezing impairs their potency. As a result, there is an increase in the prevalence of vaccine-preventable diseases in low-income countries even … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
(22 reference statements)
0
18
0
Order By: Relevance
“…An earlier study into the mechanism of ensilication showed a diffusion limited (controlled) cluster aggregation (DLCA) type process. 10 This means the more silica added to the reaction, the faster the ensilication will occur because of the abundance of polymeric silica. 33,34 This was observed by FE-SEM (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study into the mechanism of ensilication showed a diffusion limited (controlled) cluster aggregation (DLCA) type process. 10 This means the more silica added to the reaction, the faster the ensilication will occur because of the abundance of polymeric silica. 33,34 This was observed by FE-SEM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Ultimately, this study aims to further support the future application of ensilication as a novel approach to biopharmaceutical stabilisation. [8][9][10] In order to remain biologically active, the majority of protein-based biopharmaceuticals must be stored and distributed between 2-8 C in what is referred to as the 'cold chain'. Changes in temperature outside this range lead to inactivation due to cold chain failures that can oen be observed in low-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…45 At volume fractions above 24.0%, the reduced SAXS data was fitted to a ''broad-peak'' function (Fig. 1d), see eqn (2): 46,47 IðqÞ…”
Section: Assembly Of Cncmentioning
confidence: 99%
“…An ensilicated vaccine retained its immunogenicity after heat treatment or storage at room temperature for three years. 1 The technique uses silica coat to stabilize the tetanus toxoid protein in the diphtheria-tetanus-pertussis vaccine. The vaccine was immunogenic in mice after the vials were shipped within the UK by ordinary post and after heating to 100°C.…”
Section: Ensilicated Vaccines Might Improve the Cold-chain Problemmentioning
confidence: 99%